Development of Irrigation Facilities and Changing Cropping Pattern inRewari District, Haryana (1990–2021) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study analyses the impact of irrigation development on the changing cropping patterns in Rewari district, Haryana, from 1990 to 2021. Located in the semi-arid zone of southern Haryana, the district has undergone a significant shift from traditional dryland crops to irrigated and commercial crops, driven by groundwater expansion and mechanisation. Data reveal that wheat production increased from 129 (‘000 t) in 1990–91 to 166 (‘000 t) in 2020–21, while mustard and bajra showed remarkable growth of 181% and 314% respectively. In contrast, barley and pulses declined by more than 90%, indicating a shift by farmers towards more remunerative crops.The dominance of tube wells and submersible pumps has replaced canal irrigation, covering nearly 90% of the cultivated area. Although irrigation expansion enhanced productivity and crop diversification, it also led to excessive groundwater extraction and declining soil fertility. The study concludes that sustainable water management, adoption of micro-irrigation, and balanced crop diversification are essential for ensuring long-term agricultural sustainability in Rewari District.